リュツォ・ホルム湾，プリンスオラフ海岸，及びエンダビーランド地質調査報告 2021-2022（JARE-63） - 馬場, 壮太郎; ババ, ソウタロウ; Baba, Sotaro; 加々島, 慎一; カガシマ, シンイチ; Kagashima, Shin-ichi; 中野, 伸彦; ナカノ, ノブヒコ; Nakano, Nobuhiko (国立極地研究所, 2022)
第63次南極地域観測隊（JARE-63）では，2021-2022の夏期期間にリュツォ・ホルム湾，プリンスオラフ海岸，及びエンダビーランドにおいて，地質研究者3名で構成された調査隊により地質調査を行った．第63次夏期観測では，観測隊チャーターの小型ヘリコプターによる支援はなく，「しらせ」搭載の2機の大型ヘリコプター（CH-101）のみで野外観測支援がなされた．本稿では，観測計画を実施するための主に設営面での計画，準備，そして行動経過について報告する． Geological field surveys of the Lützow-Holm Bay, Prince Olav Coast, and Enderby Land were conducted by three geologists in the 63rd Japanese Antarctic Research Expedition (JARE-63) during the 2021-2022 austral summer season. Field parties were supported throughout the summer season by two main helicopters (CH-101) stationed on the icebreaker Shirase without a smaller secondary helicopter (AS350). This report summarizes field preparations and geological work and highlights several key points for future planning and research. departmental bulletin paper